Analysis of Non-Prescription Drug Services Via Telemedicine Using the Lean Six Sigma Method: Case Study in a Company Clinic - Nurmadani, Labbaika; Basabih, Masyitoh (UI Scholars Hub, 2024)
The non-compounded prescription drug service via telemedicine became an alternative solution to continue providing pharmaceutical services while simultaneously controlling physical contact in hospitals during the COVID-19 pandemic. However, after its implementation, hospitals still need to improve the effectiveness of this telemedicine service. This study aims to propose improvements to enhance the effectiveness and efficiency of non-compounded drug services via telemedicine using the Lean Six Sigma method. This method is used to identify and eliminate all waste in the business process (service) to make efficient use of time and other resources. The study uses both quantitative and qualitative approaches, with data collection through observation, document review, and in-depth interviews. The quantitative approach was used to calculate service times, while the qualitative approach was employed to explore and examine the implementation of telemedicine for non-compounded drug services. The interview results revealed at least three main problems that cause significant delays in drug service processes, namely: drug requests not being processed through the system, incomplete patient data, and delays in doctors' confirmations regarding medication changes. Observations showed that the average service time for non-compounded drug prescriptions via telemedicine is 1 hour, 37 minutes, and 11 seconds, with value add activities taking 32 minutes and 39 seconds (33.6%) and non-value-added activities taking 1 hour, 4 minutes, and 32 seconds (66.4%). The identified waste includes overprocessing, waiting, motion, and defects, leading to proposed improvements such as work standardization, flowchart refinement, 5S, and Kaizen.